Investigation of Cervical Tumor Biopsies for Chromosomal Loss of Heterozygosity (LOH) and Microsatellite Instability (MSI) at the HLA II Locus in HIV-1/HPV Co-infected Women - Chambuso, Ramadhani; Kaambo, Evelyn; Denny, Lynette; Gray, Clive M.; Williamson, Anna-Lise; Migdalska-Sęk, Monika; Agenbag, Gloudi; Rebello, George; Ramesar, Raj (Frontiers in Oncology, 2019)
Background A subset of women who are co-infected with human immunodeficiency virus type 1 (HIV) and human papillomavirus (HPV) progress rapidly to cervical disease regardless of high CD4 counts. Chromosomal loss of heterozygosity (LOH) and microsatellite instability (MSI) are early frequent genetic alterations occurring in solid tumours. Loss of an allele or part of a chromosome can have multiple functional effects on immune response genes, oncogenes, DNA damage-repair genes and tumour suppressor genes. To characterise the genetic alterations that may influence rapid tumour progression in some HIV positive women, we have compared the extent of LOH and MSI at the HLA II locus on chromosome 6p in cervical tumour biopsy DNA samples with regard to HIV/HPV co-infection in South African women. Methods A total of 164 women with cervical disease were recruited for this study, of which 74 were HIV positive and 90 were HIV seronegative. DNA from cervical tumours and matched buccal swabs were used for analyses. Chromosomal single locus assay by capillary array electrophoresis DNA microsatellites analyses was used to study LOH and MSI with six fluorescently-labelled oligonucleotide primer pairs in a multiplex PCR amplification. Pearson chi-squared test for homogeneity of proportions using an exact p value, a two-proportion Z-score test, ROC curves and a logistic regression model were used for statistical analyses. All p-values were corrected for false discovery rate (FDR) by Benjamini-Hochberg test and the adjusted p-values (q-values) were reported. All tests were significant when both p and q<0.05. Results Tumour DNA from HIV/HPV co-infected women demonstrated a higher frequency of LOH/MSI at the HLA II locus than tumour DNA from HIV seronegative women at 6p21.21 (D6S2447, 74.2% versus 42.6%; p=0.001, q=0.003), 6p21.31 (D6S2881, 78.3% versus 42.9%; p=0.002, q=0.004), 6p21.32 (D6S2666, 79% versus 57.1%; p=0.035, q=0.052), and 6p21.33 (D6S2746, 64.3% versus 29.4%; p<0.001, q<0.001), respectively. Conclusions HPV infection alone can induce LOH/MSI at the HLA II locus in cervical tumour DNA, whereas HIV co-infection exacerbates it, this may accelerate cervical disease progression in a subset of HIV positive women.